The Regressive Demands of Demand-Driven Development - Baird, Sarah; McIntosh, Craig; Ozler, Berk (2012)
Despite their explicit focus on reaching the poor, many community driven development (CDD) projects have been found to be only mildly pro-poor in their funding allocations. This paper presents evidence of an explanation that has been overlooked in the CDD literature to date: the requirement that beneficiaries must apply for projects in order to receive support. The authors first examine data on the universe of project applications and funding under Tanzania's flagship CDD program, Tanzania's Social Action Fund, and then use a census of 100 program villages to examine the determinants of both program awareness and program participation at the household level. The data paint a consistent picture at both levels: wealth, access to information, and political capital are important correlates of the ability to navigate the application process successfully. The centrally dictated features of this decentralized program appear to be the most effective mechanisms in directing funds to the poor. The results suggest that unless demand-driven projects can develop ways of soliciting engagement from a broader cross-section of the population, they are unlikely to achieve truly progressive targeting.